Learning With Mobile Technologies, Handheld Devices, and Smart Phones 2012
DOI: 10.4018/978-1-4666-0936-5.ch001
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Exam System – MES

Abstract: As the mobile applications are constantly facing a rapid development in the recent years especially in the academic environment such as student response system (Lópeza, Royoa, Labordab, & Calvoa, 2009; Ngai & Gunasekaran, 2007; Mary & Biju, 2008; Nayak & Erinjeri, 2008; Roth, Ivanchenko, & Record, 2008; Lu, Stav, & Pein, 2009; Lu, 2009; Turning Technologies, 2010) used in universities and other educational institutions; However, an effective and scalable Database Management Syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
(12 reference statements)
0
2
0
1
Order By: Relevance
“…The results showed that using pedagogical approaches in mobile learning has an overall large effect size ( g = 0.93) on learning performance. This might be due to the various interactive and smart features provided by mobile devices that make teaching methods more innovative (Lu, 2012) and, consequently, achieve better learning performance. Particularly, PBL was the most effective pedagogical approach, as it achieved a huge ( g = 2.07) effect on learning performance.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that using pedagogical approaches in mobile learning has an overall large effect size ( g = 0.93) on learning performance. This might be due to the various interactive and smart features provided by mobile devices that make teaching methods more innovative (Lu, 2012) and, consequently, achieve better learning performance. Particularly, PBL was the most effective pedagogical approach, as it achieved a huge ( g = 2.07) effect on learning performance.…”
Section: Discussionmentioning
confidence: 99%
“…Such traditional methods are the use of username/password, and/or the use of a card or badges. Other techniques depend upon biometric features which depend on unique features or characteristics owned by individual and differ them from the other, like finger print, face recognitions, DNA, Palm hand…etc., these features are distinctive and measurable [6] [23].…”
Section: Introductionmentioning
confidence: 99%
“…Esta situación ha contribuido a la disminución del analfabetismo digital y al mejoramiento de las competencias digitales de los individuos (Kneidinger -Müller, 2019). Estos factores, que abarcan el desarrollo y la sofisticación de los dispositivos móviles como smartphones y tabletas, así como el fortalecimiento de las competencias digitales de las personas, han generado nuevas áreas de investigación en el ámbito de la formación (Lu, 2012;Parsons, 2012).…”
Section: Tecnología Aprendizaje Y Conocimientounclassified